THE INFLUENCE OF EMOTIONAL QUOTIENT (EQ), SPIRITUAL QUOTIENT (SQ), PARENTAL SUPPORT AND SCHOOL ENVIRONMENT ON THE DISCIPLINE OF STUDENTS OF SMA BATIK 1 SURAKARTA - Witria Kusuma Dewi; Bambang Mursito; Kartika Hendra Titisari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Discipline is one of the aspects that will be needed to support success in any aspect, including in the process of education and learning. Emotional intelligence, spiritual intelligence, parental support and the school environment as factors that can affect a student's discipline. Emotional intelligence, spiritual intelligence, parental support and the school environment are factors that can affect a student's discipline. Type of research explanatory research was conducted with quantitative approach. Data collection technique was used instruments in the form of questionnaires. Data analysis techniques use multiple linear regression analysis. The results showed that emotional intelligence, spiritual intelligence, parental support, and school environment both simultaneously and partially significantly affect the discipline of students of SMA Batik 1 Surakarta (p value < 0.05). Keywords: discipline, emotional intelligence, spiritual intelligence, parent’s support, school environment